2008
DOI: 10.3989/gya.2008.v59.i2.499
|View full text |Cite
|
Sign up to set email alerts
|

Influencia de un pienso con castañas y pulpa de remolacha azucarera en la composición lipídica del lacón gallego

Abstract: RESUMENInfluencia de un pienso con castañas y pulpa de remolacha azucarera en la composición lipídica del lacón gallego.El objetivo del presente trabajo fue determinar el efecto de la inclusión de castañas y pulpa de remolacha en la alimentación del cerdo sobre diferentes aspectos lipídicos de los músculos externos e internos de los lacones gallegos. Dicha inclusión no modificó el contenido de lípidos, ni la proporción de glicéridos, fosfolípidos y ácidos grasos libres; sin embargo, sí causó un descenso de los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
2
2
Order By: Relevance
“…More concretely, the inclusion of chestnuts in the finishing diet seemed to increase the value of TBARS. These outcomes do not agree with those shown previously by Cobos et al [ 52 ] and Díaz et al [ 53 ], who observed that the inclusion of chestnuts reduced the TBARS index in pork meat and its derivates. At the same time, our research also do not agree with other studies that did not find any significant difference in lipid oxidation after using chestnuts in pig fattening [ 54 , 55 , 56 , 57 ].…”
Section: Resultscontrasting
confidence: 90%
“…More concretely, the inclusion of chestnuts in the finishing diet seemed to increase the value of TBARS. These outcomes do not agree with those shown previously by Cobos et al [ 52 ] and Díaz et al [ 53 ], who observed that the inclusion of chestnuts reduced the TBARS index in pork meat and its derivates. At the same time, our research also do not agree with other studies that did not find any significant difference in lipid oxidation after using chestnuts in pig fattening [ 54 , 55 , 56 , 57 ].…”
Section: Resultscontrasting
confidence: 90%
“…Within SFA, palmitic acid (C16:0) was the most abundant fatty acid (representing about 65% of total SFA) with values of 24.07, 20.43 and 20.60 g·100 g −1 for C, CH15 and CH25 treatments, respectively. These findings are in agreement with those previously reported by Cobos et al (2008) in lacón and Bermúdez et al (2012) in ham. It was found from the Pearson correlation test that SFA content was positively correlated with C16:0 (r=0.973, P<0.01).…”
Section: Resultssupporting
confidence: 94%
“…This incident could be due to the limited absorption that some of the antioxidant compounds present in the chestnut could suffer, since, for example, it has been observed that substances that have thiol groups, which show antioxidant capacity, are absorbed in a limited way [ 87 ]. Furthermore, the higher antioxidant activity found in pigs fed commercial feed also contrasts with the results obtained in several investigations on antioxidant status of pigs fed chestnut, because several authors showed that the inclusion of chestnut in the finishing diet improved lipid oxidation in different pig matrices [ 24 , 26 , 27 , 28 ]. Simultaneously, our investigation also does not agree with other works that did not show any significant difference in lipid oxidation after using chestnuts in pig fattening [ 30 , 88 , 89 ].…”
Section: Resultscontrasting
confidence: 58%
“…This characteristic, although it is beneficial for health, could have a detrimental effect on meat, because unsaturated fatty acids are easily susceptible to oxidation [ 3 ]. Nevertheless, this situation has not been displayed in preliminary studies [ 24 , 26 , 27 , 28 ]. In this way, Cobos et al [ 27 ] observed that the inclusion of 15% chestnut flour in a pig diet decreased the lipid oxidation of a dry-cured pork foreleg.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation